Condições de segurança do trabalho no Vale do Taquari para empresas de pequeno porte - Capra, Marcelo (Universidade do Vale do Rio dos Sinos, 2016)
This article aims to analyze how occupational safety conditions in the companies of the Taquari Valley. Applied was a Questionnaire on the conditions and occupational safety knowledge. Participated 25 companies from different branches and different sizes. For the result of the questionnaire were prepared graphics individuals each question quantitative way..
Keywords: Segurança do trabalho; Vale do Taquari; Questionário; Empresa; Workplace safety; Questionnaire; Company